Investigation on the Optimum Design of Heat Exchangers in a Hybrid Closed Circuit Cooling Tower - Sarker, MMA (Journal of Mechanical Engineering, 2008)
Investigation on the optimum design of a heat exchanger in a Hybrid Closed Circuit Cooling Tower having a rated capacity of 1RT is performed experimentally. The heat exchanger of dimension 0.4mx0.33mx0.572m has 15x7 bare type 15.88mm OD copper coils in staggered arrangement. The relevant design parameters were selected based on the typical East Asian meteorological constrains for the year-round smooth operation of the cooling tower. This study presents results related to the cooling capacity and the cooling efficiency with respect to wet bulb temperature and pressure drop with respect to air inlet velocity. Results are also presented in terms of number of transfer units (NTU). Cooling capacity was found to be close to the rated one for the wet mode but low in dry mode operation. Keywords: Hybrid closed circuit cooling tower, Cooling capacity, Wet mode, Dry mode doi:10.3329/jme.v37i0.820 Journal of Mechanical Engineering Vol.37 June 2007, pp.52-77